A system of exercises to develop writing abilities in 7th grade at Ricardo Zenón Secondary School - Chaviano Álvarez, Lázaro Jesús (Universidad de Ciencias Pedagógicas "Félix Varela Morales", 2011)
This major paper deals with the teaching of the writing skill in seventh grade, particulary writing as instrumental skill. A distinction is made between the concepts writing as an end, that is, writing for communicative purposes, and writing as a means, that is, writing as an instrumental skill for the reinforcement of the oral skills through the written practice of grammar, vocabulary, phoneme-grapheme relationship, etc. Writing as an instrumental skill highlighted as a preparatory step in order to move on to communicative writing in learning English as a foreign language. The paper presents the theoretical foundations that account for the importance of instrumental writing (Chapter 1),the assessement of student’s needs in terms of the development of this skill and of the teacher’s needs in terms of preparation for the teaching of this skill (Chapter 2), and a set of instrumental writing activities aimed and contributing to the student’s development of this skill (Chapter3)

Este trabajo trata sobre la enseñanza de la escritura en séptimo grado, particularmente la escritura como una habilidad instrumental. Una distinción hecha entre el concepto de escritura como un fin, que es, escritura para propósitos comunicativos, y escritura como un medio, que es , escritura como una habilidad instrumental para el reforzamiento de la habilidad oral a través de la práctica escrita de gramática, vocabulario y de la relación fonema -grafema etc. La escritura como habilidad instrumental es destacada como un paso preparatorio a fin de continuar con la escritura comunicativa en la enseñanza del inglés como idioma extranjero. Este trabajo presenta las fundaciones teóricas que cuentan para la importancia de la escritura instrumental (Capítulo 1). La valoración de las necesidades de los estudiantes en términos de el desarrollo de esta habilidad y de las necesidades de los profesores en términos de preparación para la enseñanza de esta habilidad (Capítulo 2). Y un set de actividades de escritura con el objetivo de contribuir al desarrollo de esta habilidad (Capítulo 3)
Keywords: Secundaria Básica; Escritura; Inglés; Enseñanza; Learning